Shake That Moneymaker: Insights from Montreal’s Uber Drivers - Rabih Jamil; Yanick Noiseux (Revue Interventions Économiques)
This article presents the results of an ongoing ethnography of Uber drivers in Montreal. It draws on Jean-Pierre Durand’s “job centrifugation dynamic” (Duran, 2004) conceptual framework and offers a critique of Uber’s model of labour organization which promises “good money” and claims to create a “flexible” and “no boss” work environment. Deconstructing the Uber narrative, it exposes the central features - precarity, market control scheduling and app-subordination - which structures drivers’ daily work routines and highlights twofold process of “accumulation by dispossession”(Harvey, 2004). On the one hand, drivers’ de-proletarianization is dispossessing them from all sorts of labour protection/benefits or bargaining power. And secondly, because drivers are obliged to give the organization an unconditional access to efficiently exploit their own assets (cars/phones/Internet connection), they are being dispossessed from the value of their “dead labour” embodied in their private properties which are being monetized (Kenney and Zysman, 2016), exploited and consumed as part of the Uber process of value production.